Whither global rules for the internet? the implications of the World Conference on International Telecommunication (WCIT) for international trade - Samarajiva, Rohan; Lee-Makiyama, Hosuk (European Centre for International Political Economy, 2012)
The International Telecommunications Union (ITU) will be renegotiating its binding rules, known as the International Telecommunication Regulations (ITRs) at the World Conference on International Telecommunication (WCIT) in Dubai this December, which will be the first principal update since 1988. As the current rules do not reflect or take into account the development of the data-driven economy, for consideration propose increased regulation and access charges that could set back the tremendous progress made in electronically connecting billions of people across the world through decades of liberalisation policies. However, many ITU negotiators seem to neglect their commitments under the World Trade Organization (WTO) and its General Agreement on Trade in Services (GATS) that remain in force, regardless of the provisions under the new ITRs. Each country's specific commitments in the WTO determine their obligations to provide market access (for both international interconnection and investments) under non-discriminatory terms, and 82 countries have also unilaterally agreed to open up and refrain from discriminatory measures in a so-called reference paper on basic telecommunications. Furthermore, most countries have made commitments that forbid them from imposing restrictions on the most common forms of Internet services, and a moratorium on tariffs and equivalent fees on data transmissions (known as the WTO e-commerce moratorium) which explicitly forbids access fees for data whether they are discriminatory or not. A violation of these WTO commitments may lead to trade retaliation from the WTO's near-universal membership sanctioned by its dispute-settlement mechanism. The moratorium is also politically linked to pledging not to pursue certain types of intellectual property violation cases against developing countries
Keywords: IT-Recht / (DE-627)091354080 / (DE-STW)18433-0; Telekommunikationsrecht / (DE-627)091394570 / (DE-STW)18643-3; Verhandlungen / (DE-627)091397405 / (DE-STW)16440-6